Analiza dyskursu medialnego w Polsce na temat emigracji poakcesyjnej (2004-2013): Raport z badań - Magdalena Lesińska; Justyna Pokojska (University of Warsaw, Centre of Migration Research (CMR), 2015)
– The main aim of the paper is to analyse the media discourse concerning the emigration of Poles after the Polish accession to the European Union in 2004. The source material includes the contents of two popular titles of daily press: Gazeta Wyborcza and Rzeczpospolita in a period of ten years (2004-2013). Particular attention was devoted to the periods of election campaigns to the parliament, which took place in the years 2005, 2007 and 2011. The main questions that were raised in the course of the analysis include: the image of emigration after the accession which dominates in the press, the most current and topical topics present in the media discourse, evaluation of the process of emigration and its effects and the dynamics of discourse over time.
Keywords: 330; media discourse; content analysis; post-accession of emigration of Poles